2016
DOI: 10.1194/jlr.d063735
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phthiocerol and phthiodiolone dimycocerosate esters of M. tuberculosis by multiple-stage linear ion-trap MS

Abstract: This article is available online at http://www.jlr.org Both phthiocerol/phthiodiolone dimycocerosate (PDIM) esters and phenolic glycolipids (PGLs) are dimycocerosate esters (DIMs) produced by pathogenic mycobacteria. PDIMs were originally isolated from Mycobacterium tuberculosis (1)(2)(3)(4) and are specifi c tuberculosis biomarkers ( 5, 6 ). They are among the most abundant lipids in the cell wall of various pathogenic mycobacteria, including M. tuberculosis , M. bovis , M. leprae , M. kansasii , M. microti ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…11. The normalized spectra were presented in Figure 3, where the ESI/MS spectra contain the homologous [M+NH 4 ] + ions of PDIM, ranging from m/z 1250 to 1550 (i.e., ions of m/z 1343, 1357, 1371, 1385, 1399, 1413, etc) 49 .…”
Section: Methodsmentioning
confidence: 99%
“…11. The normalized spectra were presented in Figure 3, where the ESI/MS spectra contain the homologous [M+NH 4 ] + ions of PDIM, ranging from m/z 1250 to 1550 (i.e., ions of m/z 1343, 1357, 1371, 1385, 1399, 1413, etc) 49 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, we demonstrated that sulfolipid II in Mycobacterium tuberculosis (M. tuberculosis) H37Rv cells is the predominated lipid family, consisting of hundreds of molecular species rather than the sulfolipid I family as previously reported [8,9]. LIT MS n with high resolution mass spectrometry has also been successfully applied to delineate the structures of phosphatidylinositol mannosides (PIMs) [10,11], and phthiocerol dimycocerosates (PDIMs) [12] in the cell envelope of M. tuberculosis. The former lipid family is known to have played important roles in M. tuberculosis adhesins that mediate attachment to nonphagocytic cells [13], while the latter is recently found to play role in drug resistance to M. tuberculosis [14].…”
Section: Introductionmentioning
confidence: 52%
“…tuberculosis strain H37Rv were grown and total lipids were extracted and isolated as previously described [8]. Briefly, the total lipid was separated by a Phenomenex C18 Kinetex (100 × 4.6 mm, pore size 100 Å, particle size 2.6 µm) column at a flow rate of 300 µL/min with a gradient system as previously described [12]. DAT (eluted at 24.45-26.43 min) fraction from three injections (~200 µg total lipid/injection) were collected and pooled, dried under a stream of nitrogen, and stored at −20 • C until use.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Thus, using solid media for passages may allow the preservation of PDIM positive strains. Dedicated methods to test lab strains for the presence of PDIMs are thin-layer chromatography and mass spectrometry, both of which can be coupled with NMR spectroscopy for complete characterization [48,116]. For an easier and relatively faster routine procedure, lab strains could be tested indirectly for the presence of PDIMs by drug-susceptibility assay, using drugs shown to be more potent on PDIM-depleted strains such as vancomycin [55].…”
Section: Loss Of Pdims In Vitromentioning
confidence: 99%